A psychometric evaluation of the career decision making self-efficacy scale - Purnama, Chandra Yudistira; Ernawati, Linda (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
The assessment tool for a career currently being developed requires special treatment from a psychologist/psychometrist. The measurements are conducted when students are confused about career options. However, for students who have decided, it is uncommon for them to seek professional help. Psychological tools that focus on capturing information about students' maturity in relation to their ability to make career decisions can help them choose a major that is suitable for their career. This study concerns adapting the career decision-making self-efficacy (CDMSE) that can predict one's confidence in his/her ability to make career choices. The adaptation of this instrument went through several stages such as translation, back translation, testing the reliability, and testing the validity evidence of content and internal structure using confirmatory factor analysis (CFA). This study used a sample of 539 high school students in Bandung and Cimahi. The construct reliability (CR) of the instrument was Î±=0.929. The evidence for internal structure using CFA showed that the CDMSE scale has an acceptable goodness of fit index. The standardized loading factor item is in the range 0.710-0.998. It can be concluded that the Bahasa Indonesia version of the CDMSE scale has good psychometric properties and can be used for research or assessment to measure a person's degree of confidence about his/her ability to make career choices.